Congenital heart disease – don't forget the aorta Angeborene Herzfehler – die Aorta nicht vergessen - Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Meierhofer, C.; Freilinger, S.; Weyand, Michael; Ewert, P.; von Kodolitsch, Y. (Chirurgische Praxis, 2023)
Patients with congenital heart disease (CHD) are considered chronically ill. Despite the growing body of evidence for the relevance of aortic disease in the context of CHD, it is vastly neglected. An aortopathy can have a major negative impact on morbidity and mortality, depending on the underlying heart defect and the patient’s age. Therefore, all affected patients require a life-long follow-up and access to state-of-the art specialized care. Future goals consequently aim to an increased awareness both in caregivers and patients for aortic affections and complications in patients with CHD.
CRIS-Team Scopus Importer:2023-10-20
Keywords: aortic aneurysm; aortic dilatation; aortopathy; congenital heart disease; connective tissue disease; hereditary aortic disease